The Use of a Double Suture and Conjunctival Cuts in the Lateral Tarsal Strip: A New Approach to Involutional Ectropion. Issue 8 (November 2018) - Meduri, Alessandro; Inferrera, Leandro; Oliverio, Giovanni William; Tumminello, Giuseppe; Rechichi, Miguel; Mazzotta, Cosimo; Frisina, Rino; Kaufman, Stephen; Aragona, Pasquale
Abstract : Purpose: To describe the use of a double suture and conjunctival cuts in the lateral tarsal strip (LTS) and to evaluate postsurgical outcome in patients with severe involutional ectropion. Methods: A prospective randomized study was conducted on 16 eyelids of 8 patients with symptomatic severe involutional ectropion. The 8 patients were between 62 and 79 years. They were distributed into 2 groups consisting of 4 patients each. The control group was treated with a conventional lateral tarsal strip (C-LTS), the second group underwent a modified lateral tarsal strip (M-LTS). The mean follow-up was 18 months. Success was defined as relief in lid laxity. The recurrence rate was also evaluated. Results: Patients treated with M-LTS showed lower horizontal laxity (3.5 ± 0.2) than patients treated with C-LTS (5.7 ± 0.2). During the 18-month follow-up, a statistically significant difference was found between the 2 groups with P value <0.05. Conclusions: The use of a double suture and conjunctival cuts in the lateral tarsal strip proposed by Meduri showed a reduction of postsurgical ectropion's grade and postsurgical recurrences. This technique could be used for the treatment of patients with a severe ectropion.